Transformational leadership of the administrators influence on the success of the use of information technology. In Nong Khaem District Office Bangkok. - Photikul, Anan (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this research is study the transformational leadership of the administrators that influence the success of using information technology in Nong Khaem District Office. Bangkok In this research, the researcher used quantitative data methodology, using questionnaires to collect data from 569 people and 311 samples, including 103 Bangkok civil servants. 208 people and permanent employees, calculated from the formula of Taro Yamane and using cluster random sampling method to obtain appropriate samples for data collection. Data analysis The researcher processed with the software package for social science research. And use inferential statistics to test hypotheses, including stepwise multiple regression analysis Research hypothesis test results It was found that the transformational leadership of good leaders, must be a good example for others, the organizational adjustment to the desired direction. And the orientation of the organization to the future influences the success of using information technology in Nong Khaem District Office Bangkok, in order of influence from descending Can write the regression equation as follows The success of the use of information technology = 1.053 + 0.298 (good leaders must be good examples for others) + 0.225 (organizational adjustment to the desired direction) + 0.212 (organization orientation to the future) Both the transformational leadership of the three executives can predict the success trend of using information technology by 53.90 percent Article history : Received 13 January 2019 Revised 3 March 2019 Accepted 7 March 2019 SIMILARITY INDEX = 1.74